The exchange experience on visitors' satisfaction and revisit intentions - Tan, Kenneth Kah Min (2019)
Over the years, many studies have been done in relation to tourists and service providers in the hospitality industry in order to establish how to best measure the determinants of an individual’s overall satisfaction with an experience, as well as the major influences that direct behavioral intentions such as those of revisitation. Of particular interest in this study is the exchange student population, one that is often overlooked in light of more significant target segments such as the typical tourist. However, the creation of a memorable experience has the potential to entice exchange students to return in the future, resulting in a multi-fold economic benefit that goes beyond the duration of their exchange program. This study aims to establish the determining factors regarding overall satisfaction and future revisit intentions of exchange students, while also identifying methods that may contribute to higher scores in both variables. The results are analyzed through SPSS and AMOS software, and suggestions for institutions on how to improve exchange students’ satisfaction levels and revisit intentions are proposed.